Becoming futile: the emotional pain of treating COVID-19 patients - Rodriquez, Jason (Frontiers in Sociology, 2023)
The COVID-19 pandemic has had a profoundly detrimental impact on the emotional well-being of health care workers. Yet much less is known about the specific social processes that have generated these outcomes. This article draws from 40 interviews with intensive care unit (ICU) staff in units that were overwhelmed with COVID-19 patients to understand how one social process in particular, the act of treating critically ill COVID-19 patients, impacted their emotional well-being. Findings show that the uncertainty of how to effectively treat these patients, given the lack of standard protocols combined with the ineffectiveness of treatments they tried, resulting in an unprecedented scale of deaths, caused significant moral distress and contributed to emotional exhaustion, depersonalization, and burnout. Furthermore, treating uncurable patients undermined their occupational identities as effective health care professionals.While recent studies of the emotional socialization of health care workers have portrayed clinical empathy as a performative interactional strategy, the findings show empathy to be more than dramaturgical and, in this context, entailed considerable risk to workers' emotional well-being.